Implementasi Akhlak Kepada Allah Swt Dalam Kehidupan Sehari-Hari Mahasiswa - Amanda Amanda; Bias Tirta Bayu; Wismanto Wismanto; Al Hamida; Atik Devi Kusuma (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
Of the many students today, many of them have forgotten their obligations as God's creatures. It is believed that bad things will happen to students if this is allowed to continue. Therefore, it is important to instill the principles of moral education in every student. The aim of this research is to find out incorporation of creation-based morality into students' daily lives. This research uses a qualitative descriptive methodology using a literature review and questionnaire. Thirty students registered from state and private universities in semesters 1 to 8 were used as research subjects. Morality derives its etymology from the words character, behavior and manners. For God, morality refers to what is right and appropriate to do.